2015
DOI: 10.1186/s12879-015-0846-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the high rates of extrapulmonary tuberculosis in Ethiopia reveals no single driving factor and minimal evidence for zoonotic transmission of Mycobacterium bovis infection

Abstract: BackgroundEthiopia, a high tuberculosis (TB) burden country, reports one of the highest incidence rates of extra-pulmonary TB dominated by cervical lymphadenitis (TBLN). Infection with Mycobacterium bovis has previously been excluded as the main reason for the high rate of extrapulmonary TB in Ethiopia.MethodsHere we examined demographic and clinical characteristics of 953 pulmonary (PTB) and 1198 TBLN patients visiting 11 health facilities in distinct geographic areas of Ethiopia. Clinical characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 50 publications
6
66
3
1
Order By: Relevance
“…This agreed with different findings reported in Ethiopia and aboard 5,[10][11][12][13] . The possible reason might be related with, lower rates of notification of TB among women than men due to low health seeking behavior, lack of financial control and stigma associated with being TB positive 2 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This agreed with different findings reported in Ethiopia and aboard 5,[10][11][12][13] . The possible reason might be related with, lower rates of notification of TB among women than men due to low health seeking behavior, lack of financial control and stigma associated with being TB positive 2 .…”
Section: Discussionsupporting
confidence: 82%
“…The other justification goes in line with Berg et al, study justified that regular and direct contact with live animals, was a significant risk factor for EPTB 21 . These factors also seem likely, because, people in the study area are known live stock keepers and due to their local tradition, most of their domestic animals shared human shelter.…”
Section: Discussionsupporting
confidence: 65%
“…This might be due to the statistical pooling effect of the reference groups. In contrast to our study, other studies have shown an association between HIV co-infection and TB treatment outcome [27,35].…”
Section: Discussioncontrasting
confidence: 53%
“…However, there are similar reports showing lower notification rates of PTB+ cases and high numbers of EPTB cases in the northern part Ethiopia [3, 13-15, 25, 26]. The causes for this are not yet identified and some reports suggest that it might have something to do with the host genomic base, but this needs further investigation [27]. On top of this, due to limited resources, most of the health facilities in Ethiopia have been using AFB microscopy, which has low sensitivity (40-45%) and might contribute to lower notification rates of PTB+ (observation).…”
Section: Discussionmentioning
confidence: 85%
“…However, some particular M. bovis strains have adapted to the human host with the ability to transmit between immune-compromised individuals, as discussed later in this chapter. Even in countries with a very high incidence of livestock TB caused by M. bovis and high incidence rates of extrapulmonary TB in humans, human infection with M. bovis is excluded, as different lineages of M. tuberculosis are considered responsible for extrapulmonary TB (7).…”
Section: Introductionmentioning
confidence: 99%